2018
DOI: 10.1007/s00455-018-9889-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Swallowing with Videofluoroscopy in Patients with Locally Advanced Head and Neck Cancer After Chemoradiation

Abstract: The aim of this study was to investigate the prevalence, severity, and pattern of evolution of swallowing impairments encountered in head and neck cancer (HNC) patients before and after chemoradiation (CRT) with videofluoroscopy of swallowing study (VFSS), using the modified barium swallow impairment profile (MBSImP) protocol and scoring system, and to determine the appropriate time points in which these patients should undergo VFSS post-CRT. A prospective cohort of 69 patients with locally advanced HNC underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 62 publications
3
31
1
2
Order By: Relevance
“…12,13 The high prevalence of OD and its consequences on health-related quality of life in this population asks for early detection of this condition in order to facilitate early implementation of swallowing rehabilitation and nutritional support. [14][15][16] Often, it remains unclear which patients should be monitored for OD and at what time points. 17 It can be expected that fewer complications of OD will arise if the nature of OD and the nutrition status are systematically monitored during the HNC follow-up visits.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The high prevalence of OD and its consequences on health-related quality of life in this population asks for early detection of this condition in order to facilitate early implementation of swallowing rehabilitation and nutritional support. [14][15][16] Often, it remains unclear which patients should be monitored for OD and at what time points. 17 It can be expected that fewer complications of OD will arise if the nature of OD and the nutrition status are systematically monitored during the HNC follow-up visits.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It was confirmed that RAD is characterized by deviations in the base of the tongue, laryngeal vestibule closure, laryngeal elevation, and aspiration. 16,17 A possible explanation for reduced TS may be the changed structure of the tongue. As the tongue consists of types I and II muscle fibers, 18 with type II muscle fibers being sensitive to early RT injury, 9 it can be assumed that TS will be affected by RT.…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature and personal consultation with a specialist in otolaryngology indicates that there is no consensus regarding a protocol for performing VFSS in people with dysphagia (personal communication with Peter Belafsky MD, PhD, Medical Director of the Voice and Swallowing Center University of California, Davis). Unalike protocols are reported by different institutions in the United States currently publishing in this area of research (2325) although protocol consensus may be consistent loco-regionally or in different countries. The method for assessment of VFSS studies is also not standardized in people despite the fact that a comprehensive set of quantitative measures have been developed, reported and validated (26).…”
Section: Discussionmentioning
confidence: 99%